Lactation Intervention Study at Workplace; A Narrative Review - Nur Adliyani, Zaraz Obella; Basrowi, Ray Wagiu (Journal of Indonesian Specialized Nutrition, 2023)
Every year, there is an increase in the number of female workers in Indonesia, most of whom are of productive age. There are quite a few women who breastfeed. With the role of being both a mother and a worker, quite a few problems arise, one of which is the problem of exclusive breastfeeding as a working mother. Method: The literature search for this article review assignment was carried out during November 2023 by searching on the Google Scholar site and obtaining seven journals from publication years 2014 to 2022. From several journals that have been reviewed, it was found that working mothers who breastfeed have several challenges in providing exclusive breastfeeding, including internal, external, knowledge, and education factors. In terms of internal factors, it can be the stress experienced or the feelings the mother faces—external factors include lack of attention from the external environment. In terms of knowledge, many working mothers still do not understand the importance of breastfeeding while working. Meanwhile, in terms of education, it also influences exclusive breastfeeding among working mothers. Several factors and challenges working mothers encounter in providing exclusive breastfeeding can be prevented and overcome in several ways. This can be done by educating working mothers before and while breastfeeding. Moreover, it can also be used by companies where the mothers work to provide space and time for breastfeeding mothers who want to express breast milk at work.